Exploring the Dynamics of Student Motivation and Behavior: A Qualitative Analysis of Influencing Factors and Effective Interventions - Mahmudulhassan; Muhammad Abuzar; Saif Uddin Ahmed Khondoker; Obydur Rahman (Solo Universal Journal of Islamic Education and Multiculturalism, 2024)
Objective: This study investigates the key factors influencing student motivation and behavior in higher education, with a specific emphasis on student engagement, counseling, and mental health services. The main objective is to understand how these components contribute to students’ academic and personal development, enhance their learning experiences, and foster a healthy and inclusive campus environment. Theoretical framework: The theoretical framework draws from Self-Determination Theory (SDT), which highlights the significance of autonomy, competence, and relatedness in motivating individuals. Literature review: The literature review supports the role of student-centered support systems, particularly mental health and counseling services, as essential for academic persistence and emotional resilience. Methods: A qualitative research approach was adopted, employing focus groups and in-depth interviews with a diverse set of participants. These included faculty members across various disciplines, professional counselors, mental health practitioners, and students. Results: The study reveals that intrinsic motivation—fostered through an inclusive and supportive academic culture—is a major determinant of student success. Students who actively engage in academic and extracurricular activities demonstrate more positive behavior and show higher levels of motivation and resilience. Counseling and mental health services play a crucial role in helping students navigate emotional and psychological stress, thus sustaining their engagement and well-being. Implications: The findings have significant implications for higher education institutions. They underscore the need to prioritize mental health services and student engagement programs as core components of student success strategies. Institutions should create opportunities for leadership, peer support, and inclusive learning to strengthen students’ sense of belonging and community. Novelty: The novelty of this study lies in its integrated perspective, combining academic, psychological, and social dimensions to propose a holistic model for fostering student motivation and behavior.